Revisiting Ecuador's Economic and Social Agenda in an Evolving Landscape - Fretes-Cibils, Vicente; Giugale, Marcelo; Somensatto, Eduardo (Washington, DC : World Bank, 2012)
The policy notes for Ecuador are part of a series of books that the Bank prepares periodically summarizing its accumulated knowledge on the economic and social issues of member countries. The timing of the notes, early 2007, coincides with a new presidential period, which offers the country the opportunity to consolidate many of the gains of the past few years, while building the basis for a more dynamic, equitable and inclusive growth process. The analysis contained in the policy notes indicates that Ecuador is a country with great potential, with a society that has exhibited incredible resilience and the ability to adapt to new challenges. The Ecuadoran society has overcome adversity with great determination in the past few years. Periodic economic crises, external shocks, and even natural disasters tested the country's ability to cope with difficulties. Despite these challenges, the country has maintained a forward-looking perspective and has achieved some important goals. Economic stability in the past few years has given Ecuador the opportunity for a period of sustained economic growth. During this period several development indicators have improved, and several sectors of the economy have demonstrated the dynamism and entrepreneurship that are present the Ecuadoran culture. In general, surveys show that Ecuadorans feel that their individual conditions are likely to improve in the future. The notes cover many areas and subjects but are grouped into three broad themes: preserving stability and accelerating growth, promoting sustainable and equitable social development, and improving governance and strengthening institutions. The remainder of this chapter summarizes the main findings and recommendations of the policy notes.